Overview of COVID-19 Infection Manifestation in Neuropsychiatry Aspect - Dianli Fitriani (HM Publisher, 2021)
At the end of 2019, the coronavirus infection pandemic shocked the world. This virus began with reports of infections in the Wuhan area, China. The death rate from COVID-19 infection can reach 3%; however, the mortality rate in critically ill patients with COVID-19 infection is much higher, reaching 61.5%. This study was aimed to summarize the neuropsychiatric impact and neuropathological mechanisms of COVID-19 infection. The primary manifestation of COVID-19 infection is respiratory tract infection. Coronavirus can penetrate the central nervous system and cerebrospinal fluid in less than a week. Histopathological examination of the brain of the deceased COVID-19-19 showed the potential for SARS-CoV-2 to infect the central nervous system (CNS). Neuroinflammation can also damage blood brain barrier. Several patients treated with COVID-19-19 infection exhibited confusion and agitation without respiratory symptoms or other signs of infection. The COVID-19 pandemic not only directly impacts infected individuals but has also caused a new wave of psychological stress in society.